Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00414-014-1066-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of different classes of RNA molecules from formalin-fixed paraffin-embedded autoptic tissues: a pilot study

Abstract: For a long time, it has been thought that fresh and frozen tissues are the only possible source of biological material useful to extract nucleic acids suitable for downstream molecular analysis. Recently, for forensic purpose such as personal identification, also fixed tissues have been used to recover DNA molecules, whereas RNA extracted from such material is still considered too degraded for gene expression studies. In the present pilot study, we evaluated the possibility to use forensic formalin-fixed paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In particular, this trend is even more evident for miR-30d-5p because of its lower expression level in ovarian cancers. The highest fragmentation of the RNAs in Bouin’s fixative is in line with the fixative composition, which has a 9–10% concentration of formaldehyde, 5% glacial acetic acid, and 0.9% of picric acid [19], and it is in agreement also with results reported by other authors [3,4,20,21,22]. Only Gloghini and colleagues have demonstrated the detection of 921 base stretches by RT-PCR from both formalin- and Bouin’s-fixed tissues, but the sample fixation time was reduced to 5 hours [23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, this trend is even more evident for miR-30d-5p because of its lower expression level in ovarian cancers. The highest fragmentation of the RNAs in Bouin’s fixative is in line with the fixative composition, which has a 9–10% concentration of formaldehyde, 5% glacial acetic acid, and 0.9% of picric acid [19], and it is in agreement also with results reported by other authors [3,4,20,21,22]. Only Gloghini and colleagues have demonstrated the detection of 921 base stretches by RT-PCR from both formalin- and Bouin’s-fixed tissues, but the sample fixation time was reduced to 5 hours [23].…”
Section: Discussionsupporting
confidence: 91%
“…This fixation method has been used for specific purposes because it better preserves some morphological details, such as nuclear conformation [3]. In the past decades, several studies have already shown that Bouin’s-fixed samples are amenable for nucleic acid and protein analyses, but only to a certain point, as the fixative has resulted to be more detrimental compared to 10% buffered formalin mixture in the preservation of biomolecules [1,3,4]. Currently, no investigation has been carried out on the analysis performance with respect to miRNAs, despite the publication of two samples in a report [4].…”
Section: Introductionmentioning
confidence: 99%
“…These archives remain an underused resource, as NGS of FFPE biopsies was previously thought to yield results of insufficient quality. However, results comparable to those of FF samples have been obtained, even using highly degraded FFPE samples [ 28 , 29 , 30 , 31 ] Several investigations of the miRNA profile of ccRCC have been performed [ 7 , 32 ], as have studies on FFPE specimens [ 14 , 33 ]. However, to the best of our knowledge only the work of Weng et al has investigated the miRNA profile of ccRCC with NGS of samples derived from FFPE [ 28 ] Although novel, the work of Weng et al included only three cases of ccRCC and their findings, therefore, require further investigation and validation.…”
Section: Introductionmentioning
confidence: 99%
“…However, human postmortem tissue shows a high degree of biological variance [ 23 , 24 ] which may influence the results obtained by quantitative gene expression analysis. Indeed, it is well known that both antemortem (fever, hypoxia-ischemia, and acidosis) and postmortem ( postmortem interval—PMI, brain or cerebrospinal fluid pH changes) factors can influence the production of gene transcripts [ 25 29 ].…”
Section: Introductionmentioning
confidence: 99%